Development of Evidence-Based Disease Education Literature for Pakistani Rheumatoid Arthritis Patients - Naqvi, Atta Abbas; Hassali, Mohamed Azmi; Aftab, Muhammad Tariq; Shyum Naqvi, Syed Baqir; Zehra, Fatima; Ahmad, Rizwan; Ahmad, Niyaz (MDPI, 2017)
Rheumatoid arthritis affects 0.5% to 1% of the population globally and is one of the most common causes of disability. Patient education plays a key role in improving treatment outcomes. The purpose of this study was to discuss the process involved in designing an evidence-based disease education literature for rheumatoid arthritis patients of Pakistan in Urdu language with culturally relevant illustrations. A study was conducted to develop disease education literature using Delphi consensus, content validity, and patient feedback. A panel of experts comprised of university professors and health care experts, including health practitioners and pharmacists as well as a social scientist, was set up to assess the need. Eight patients were randomly selected and were asked to give their feedback. Their feedback was incorporated in the development process. The entire process was carried out in eight steps. A disease education literature for patients of rheumatoid arthritis was developed and edited in the form of a booklet. The booklet contained evidence-based information that must be provided to patients in both Urdu and English languages with culturally relevant illustrations. The availability of such literature is significant, as it enables the patients to seek knowledge at home at their convenience. This home-based knowledge support is as helpful as any other means of medical care. The developed literature is planned to be used in further studies which will evaluate its impact in improving knowledge of RA patients.